How did that get there? A population‐based analysis of nasal foreign bodies. Issue 11 (15th September 2014) - Svider, Peter F.; Sheyn, Anthony; Folbe, Elana; Sekhsaria, Vibhav; Zuliani, Giancarlo; Eloy, Jean Anderson; Folbe, Adam J.
<x xml:space="preserve">Abstract</x> Background The purpose of this study was to calculate nationwide incidence of emergency department (ED) visits for nasal foreign bodies, identify the most frequently encountered consumer products, and evaluate outcomes and demographic trends. Methods The Nationwide Electronic Injury Surveillance System (NEISS) was evaluated for ED visits related to nasal foreign bodies for the most recent 5‐year span available. Nationwide incidence was calculated, and the most frequent foreign bodies were identified and organized by demographics including age and gender. Results A total of 6418 entries extrapolated to an estimated 198, 566 ED visits nationwide were found. Out of individual case entries evaluated, median patient age was 3 years, and 42.7% of patients were male. Ninety‐six percent (96.4%) of patients were released after examination/treatment. Jewelry beads comprised a plurality of nasal foreign bodies, followed by paper products and toys. Patients with nasal foreign bodies involving toys, building sets, pens/pencils, batteries, coins, and nails/screws were predominantly male, whereas patients with nasal foreign bodies involving jewelry, paper products, and buttons were predominantly female. Jewelry was the most common item for patients in most age groups; age‐specific differences in the composition of remaining nasal foreign bodies were noted. Conclusion A variety of consumer products carry inherent risks for becoming nasal foreign bodies, with nearly 200, 000 ED visits over a 5‐year period. Jewelry beads, paper products, and toys were the most common products noted. Speedy recognition and retrieval of these items and other objects noted is imperative for avoidance of deleterious sequelae. Demographic‐specific trends noted and organized by age and gender may be an invaluable adjunct for patient history‐taking and clinical examination.